Correction to: APASL clinical practice guideline on hepatitis B reactivation related to the use of immunosuppressive therapy (Hepatology International, (2021), 15, 5, (1031-1048), 10.1007/s12072-021-10239-x) - Lau G. (2023)
Unfortunately, the first and last name of the Co-author, Tawesak Tanwandee has been interchanged in the original publication of the article. The correct first name should read as “Tawesak” and the last name should read as “Tanwandee” respectively.